Control of triple-negative breast cancer using ex vivo self-enriched, costimulated NKG2D CAR T cells - Han, Yali; Xie, Wei; Song, De-Gang; Powell, Daniel J. (Journal of hematology and oncology, 2018)
Triple-negative breast cancer (TNBC) is an aggressive disease that currently lacks effective targeted therapy. NKG2D ligands (NKG2DLs) are expressed on various tumor types and immunosuppressive cells within tumor microenvironments, providing suitable targets for cancer therapy. We applied a chimeric antigen receptor (CAR) approach for the targeting of NKG2DLs expressed on human TNBCs. Lentiviral vectors were used to express the extracellular domain of human NKG2D that binds various NKG2DLs, fused to signaling domains derived from T cell receptor CD3 zeta alone or with CD27 or 4-1BB (CD137) costimulatory domain. Interleukin-2 (IL-2) promoted the expansion and self-enrichment of NKG2D-redirected CAR T cells in vitro. High CD25 expression on first-generation NKG2D CAR T cells was essential for the self-enrichment effect in the presence of IL-2, but not for CARs containing CD27 or 4-1BB domains. Importantly, self-enriched NKG2D CAR T cells effectively recognized and eliminated TNBC cell lines in vitro, and adoptive transfer of T cells expressing NKG2D CARs with CD27 or 4-1BB specifically enhanced NKG2D CAR surface expression, T cell persistence, and the regression of established MDA-MB-231 TNBC in vivo. NKG2D-z CAR T cells lacking costimulatory domains were less effective, highlighting the need for costimulatory signals. These results demonstrate that CD27 or 4-1BB costimulated, self-enriched NKG2D CAR-redirected T cells mediate anti-tumor activity against TNBC tumor, which represent a promising immunotherapeutic approach to TNBC treatment.